FRI0451 SECUKINUMAB PROVIDES SUSTAINED IMPROVEMENTS IN THE SIGNS AND SYMPTOMS IN PSORIATIC ARTHRITIS: FINAL 5 YEAR EFFICACY AND SAFETY RESULTS FROM A PHASE 3 TRIAL. (June 2019) - Mease, Philip J.; Kavanaugh, Arthur; Reimold, Andreas; Tahir, Hasan; Rech, Jürgen; Hall, Stephen; Geusens, Piet; Pellet, Pascale; Delicha, Eumorphia Maria; Pricop, Luminita; Mpofu, Shephard
Abstract : Background: Secukinumab (SEC) provided rapid and significant improvements in all key clinical domains of psoriatic arthritis (PsA) in the FUTURE 1 study (NCT01392326 ) with improvements sustained through 3 years. 1 Objectives: We present the final 5 year efficacy and safety results of the study. Methods: Overall, 606 adults with active PsA were randomised to SEC 10 mg/kg intravenously at baseline, and at weeks (wks) 2 and 4, followed by 150 mg or 75 mg subcutaneously (SC) every 4 wks, or matching placebo. Placebo patients (pts) were re-randomised to SEC 150 mg or 75 mg SC from Wk 16 or 24, depending on clinical response. 1 At Wk 104, 460 pts entered the 3-year extension study. Pts could have SEC dose escalated from 150 to 300 mg and from 75 mg to 150/300 mg starting from Wk 156, based on physician's judgement. Assessments at Wk 260 included ACR20/50/70, PASI 90, HAQ-DI, SF-36 PCS, and resolution of dactylitis and enthesitis and are reported for pts originally randomised to the SEC 150 mg and 75 mg groups (observed data). Safety is reported as exposure adjusted incidence rate/100 patient-years (EAIR) for all pts (n = 587) who received ≥1 dose of study treatment. Results: Overall, 132/161 (82%) and 124/147 (84.4%) pts originally randomised to SEC 150/75 mg, respectively, who entered the extension study, completed 260 Wks of treatment. A total of 86/236 (36.4%) pts on SEC 150 mg were escalated to 300 mg, while 180/221 (81.4%) pts on SEC 75 mg were escalated to 150/300 mg. Clinical responses were sustained or further improved through 5 years treatment (Table 1 ). Over the entire study period (SEC mean exposure of 2320 patient-years), the safety profile of SEC was consistent with previous reports. 1 EAIR of selected adverse events for SEC were serious infections (1.8), ulcerative colitis (0.04), Crohn's disease (0.1), and MACE (0.5). Six deaths (3 in each dose group) were reported in any SEC group through 5 years. Conclusion: SEC provided sustained improvements in the signs and symptoms in the major clinical domains of PsA through 5 years. SEC was well tolerated with a safety profile consistent with that previously reported. References: [1] Mease PJ, et al. Ann. Rheum. Dis. 2017; 76 (suppl 2): 952. Disclosure of Interests: Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Arthur Kavanaugh Grant/research support from: UCB Pharma, Andreas Reimold Grant/research support from: AbbVie, Hasan Tahir: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than $10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Stephen Hall Grant/research support from: AbbVie Inc, BMS, Lilly, Janssen, Pfizer, UCB, and Novartis, Consultant for: AbbVie Inc, BMS, Lilly, Janssen, Pfizer, UCB, and Novartis, Piet Geusens Grant/research support from: Research support, consultant and/or speaker fees from: Pfizer, Abbott, Eli Lilly, Amgen, MSD, Roche, UCB, BMS, Novartis, Will-Pharma, Grant/research support from: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Consultant for: Research support, consultant and/or speaker fees from: Pfizer, Abbott, Eli Lilly, Amgen, MSD, Roche, UCB, BMS, Novartis, Will-Pharma, Speakers bureau: Research support, consultant and/or speaker fees from: Pfizer, Abbott, Eli Lilly, Amgen, MSD, Roche, UCB, BMS, Novartis, Will-Pharma, Speakers bureau: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Pascale Pellet Shareholder of: Novartis, Employee of: Novartis, Eumorphia Maria Delicha Employee of: Novartis, Luminita Pricop Shareholder of: Novartis, Employee of: Novartis, Shephard Mpofu Employee of: Novartis